Personal Perspectives on the Emergence of the Learning Sciences: 1970s–2005 - Pea, Roy; Linn, Marcia C. (Frontiers in Education, 2020)
We describe the emergence of the interdisciplinary learning sciences field and its consequential transformations, drawing on experiences that brought us together. Starting with our undergraduate years, the account culminates with the formation of the International Society of the Learning Sciences. We weave our experiences around six themes that shaped the emergence of the learning sciences and our own trajectories: (a) Broadening the community and incorporating new disciplinary perspectives; (b) Appropriating and developing new methods; (c) Reconceptualizing challenges; (d) Creating artifacts; (e) Developing abstractions; and (f) Developing people. We intend this personal account to stimulate new initiatives and deepening insights as the journey of the learning sciences continues.